Educação Ambiental no município de Uberlândia/MG: Espaços, estratégias e atos políticos do poder público municipal - Lopes, Gabriel Pereira (2023)
Environmental Education (EE) is a interdisciplinary field of study and historically dynamic, with the purpose of forming individuals capable to comprehend the complexity of socio-environmental issues. In this research, our objective was to characterize and analyze the EE initiatives implemented in Uberlandia/MG. We focused on two institutions affiliated with the Direct and Indirect Administration of the City Hall of Uberlandia (PMU): the Center for Environmental Education (NEA) and the Water Citizen School Program (PEAC). Our analysis primarily concentrated on the organizational structure of these public agencies, incorporating testimonials from environmental educators and evaluating the EE activities carried out both at formal educational places and non-formal spaces, such as municipal parks Siquierolli, Santa Luzia and Gávea. We also investigated the formulation of the Uberlandia’s Municipal Policy of Environmental Education (PMEA) and the educational strategies adopted. We conducted the study in the period from 2021 to 2022, using a qualitative approach. For data collection, we conducted semi-structured interviews with people directly involved with EE in the municipality, documentary analysis and field observations. Our findings revealed that the lack of organizational structure within the NEA has a direct impact on all areas of activity of the sector, including the implementation of educational activities. As a result, the EE in the PMU is in precarious conditions, and environmental educators feel undervalued. Another factor, there is no certainty of replacement of the NEA team when staff members retire, which further exacerbates the situation. On the other hand, the PEAC exhibits a different situation, with all positions filled, defined roles for its members, and stable funding. Both NEA and PEAC environmental educators share a similar perspective on the conception of EE, adopting conservative pedagogical practices, which are based on the transmission of information and the implementation of specific activities aimed at promoting a change in individual behavior. In this sense, the EE that has been historically consolidated in Uberlandia is still far from the critical perspective, which aims to promote the social transformation. Municipal parks play a significant role in EE in Uberlandia, serving as vital connections between the population and the critical perspective of environmental education. These environments offer a democratic opportunity to experience a multi-sensory education. However, the three parks analyzed needs infrastructure improvements and innovative proposals for the use of these environments. Insufficient investment and inadequate planning hinder the educational potential of municipal parks, limiting the creation of meaningful and enriching experiences for visitors. The implementation of PMEA, by Decree nº. 19.642, March 9, 2022, holds the potential to be an innovative instrument, able of changing the reality of EE in Uberlandia. Although, the way this normative was built, without dialogue and participation of the population in the formulation process, represents an obstacle to its effectiveness as a public policy. Engaging Uberlandia's population, represented by various sectors and social actors, is essential to ensure an inclusive and contextually appropriate PMEA.